RELATIONSHIP BETWEEN SOCIAL SUPPORT FAMILIES WITH MEANINGFULNESS OF LIFE IN THE ELDERLY IN RURAL KEBANDUNGAN - Kokom, Kokom; Edwina, Triana Noor (Universitas Negeri Makassar, 2020)
This study aims to determine the relationship between family social support and meaningfulness of life in the elderly in Kebandungan Village. The hypothesis proposed in this study is that there is a positive relationship between family social support and meaningfulness of life in the elderly who live in Kebandungan Village. The subject of this study is the elderly aged >60 (sixty years and over) who have a family including a husband, wife, siblings, children and grandchildren, both living in one house or separately. The number of subjects in this study were 65 elderly. Data collection was carried out using meaningfulness of life Scale and Family Social Support Scale. The data analysis method used is the Pearson Product Moment Correlation analysis. Based on the results of the study, obtained a correlation coefficient (rxy) = 0.397 with p = 0.01 (p <0.05) which means there is a positive relationship between family social support and meaningfulness of life. The coefficient of determination (R Squared) is equal to (R2) = 0.158, which means that the effective contribution to family social support is 15.8%, so the remaining 84.2% is influenced by other factors, namely personal understanding, acting positively, deepening tri values (creative value, appreciation value, attitude value), and worship.